The Influence Of Compensation And Organizational Culture On Employee Work Motivation In Multinational Companies - Randy Satria; Dian Indiyati (Return : Study of Management, Economic and Bussines, 2025)
Abstract: This study aims to analyze the influence of compensation and organizational culture on employee work motivation in multinational companies. Work motivation is a crucial factor that can drive optimal employee productivity and performance. This study employed a quantitative approach with the Structural Equation Modeling (SEM) analysis method. The sampling technique used the Lemeshow formula, with 115 respondents and data collection was conducted through the distribution of questionnaires with a Likert scale to predetermined respondents. The results show that compensation has a positive effect on work motivation, but this effect is at the threshold of significance. This means that adequate compensation can indeed boost work motivation, but its contribution is not dominant. Conversely, organizational culture has been shown to have a positive and significant influence on employee work motivation. A strong organizational culture, characterized by the implementation of positive values, norms, and collective behavior, can create a work environment that supports increased employee morale and motivation.